(untitled) (The Review of Diabetic Studies, 2025)
Dental emergencies, for example traumatic injuries, infections, and post-procedural complications, demonstrate a significant clinical challenge. Dental emergencies require effective recognition and management. Traumatic dental injuries (fractures, luxations, and avulsions) may cause pulp necrosis, root resorption, and tooth loss. The prognosis closely related to the timeliness of intervention. Infectious dental emergencies (often originating from untreated caries or periodontal disease) responsible for risks of local and systemic complications, for example osteomyelitis, deep neck space infections, and rarely, intracranial involvement. Post-procedural complications, such as bleeding, and alveolar osteitis, necessitate careful evaluation of systemic factors. For example, coagulopathies and medication use to prevent morbidity. Comprehensive evaluation combining patient history, clinical examination, and judicious use of imaging, for example radiographs and advanced modalities (CT or cone-beam CT). They enable confirming diagnosis and guide effective management. Early intervention, preventive strategies, and cooperation with medical providers are important to minimize complications, preserve oral structures, and enhance optimal patient outcomes.